Defending against SARS-CoV-2: The T cell perspective - Almendro-Vázquez, Patricia; Laguna-Goya, Rocío; Paz-Artal, Estela (Frontiers in Immunology, 2023)
SARS-CoV-2-specific T cell response has been proven essential for viral clearance, COVID-19 outcome and long-term memory. Impaired early T cell-driven immunity leads to a severe form of the disease associated with lymphopenia, hyperinflammation and imbalanced humoral response. Analyses of acute SARS-CoV-2 infection have revealed that mild COVID-19 course is characterized by an early induction of specific T cells within the first 7 days of symptoms, coordinately followed by antibody production for an effective control of viral infection. In contrast, patients who do not develop an early specific cellular response and initiate a humoral immune response with subsequent production of high levels of antibodies, develop severe symptoms. Yet, delayed and persistent bystander CD8+ T cell activation has been also reported in hospitalized patients and could be a driver of lung pathology. Literature supports that long-term maintenance of T cell response appears more stable than antibody titters. Up to date, virus-specific T cell memory has been detected 22 months post-symptom onset, with a predominant IL-2 memory response compared to IFN-γ. Furthermore, T cell responses are conserved against the emerging variants of concern (VoCs) while these variants are mostly able to evade humoral responses. This could be partly explained by the high HLA polymorphism whereby the viral epitope repertoire recognized could differ among individuals, greatly decreasing the likelihood of immune escape. Current COVID-19-vaccination has been shown to elicit Th1-driven spike-specific T cell response, as does natural infection, which provides substantial protection against severe COVID-19 and death. In addition, mucosal vaccination has been reported to induce strong adaptive responses both locally and systemically and to protect against VoCs in animal models. The optimization of vaccine formulations by including a variety of viral regions, innovative adjuvants or diverse administration routes could result in a desirable enhanced cellular response and memory, and help to prevent breakthrough infections. In summary, the increasing evidence highlights the relevance of monitoring SARS-CoV-2-specific cellular immune response, and not only antibody levels, as a correlate for protection after infection and/or vaccination. Moreover, it may help to better identify target populations that could benefit most from booster doses and to personalize vaccination strategies.